Charge masters and the effects on hospitals. (2nd October 2021) - Layton, Whitney; Lemmon, Katie; Coustasse, Alberto
ABSTRACT: The hospital chargemaster has been the heart of the healthcare revenue cycle, as it has served as the hospitals' starting point for billing patients and payers. The CDM was made as an extensive breakdown of the cost of the care provided and in order for a hospital to correctly bill a patient for care received as every chargeable item in the hospital must be included in the master. The methodology for this study utilized a literature review. It consisted of academic sources, electronic databases, academic journals, and government websites. Thirty-eight sources were referenced for this literature review. The literature review illustrated examples of CDMs in hospitals and how the correct coding of a visit or procedure can mean the difference in payment for a patient. It was found that the transparency of a CDM is a definite asset to the patient and facility as well. Participation with CDM throughout hospitals has shown an increase in billing consistency with hospital facilities. This literature review suggested that CDMs has increased transparency for prices and a positive increase in quality of care.